Management Through The Implementation of Multicultural Culture In Islamic Boarding Schools - Rosyadi BR; Fathor Rozi; Tarmidiyono Tarmidiyono (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Education, especially Islamic education, with a pluralist-multicultural paradigm, urgently needs to be immediately designed in the learning process. The world of semi-Islamic boarding schools or dormitories is undoubtedly no stranger to its positive and negative sides. It is often heard that the hostel is an arena for fading a sense of nationalism in the souls of the younger generation. The application of multicultural culture can be used as a method for solving problems in the souls of the younger generation. This study aimed to identify and describe the concept of character management by applying multicultural culture to male boarding schools at Madrasah Tsanawiyah 1 Probolinggo. The method used in this study uses a qualitative descriptive approach. The research results show that the concept of multicultural culture application in this institution is carried out using; a peace workshop, students' mukim design, multicultural learning and assessment. Multicultural culture can provide students with an understanding of the existing differences, but even though we are different, we can still unite to achieve a goal. The implications obtained through character management by applying multicultural culture to students can foster a sense of nationalism which is shown by caring, helping, being polite to friends and teachers and respecting each other regardless of caste or social status, through character management by applying multicultural culture in this institution become a place to instil a spirit of nationalism to unite the existing diversity. This research is a form of novelty that is unique from previous research because this study analyzes character management which involves multicultural culture.